Physician practice in food allergy prevention in the Middle East and North Africa - Yvan Vandenplas; Abdulrahman Saleh AlFrayh; Bandar AlMutairi; Mahmoud Salah Elhalik; Robin J. Green; Joseph Haddad; Emad Abdulqader Koshak; Mohamad Miqdady; Nezha Mouane; Mohamed Salah; Gamal Samy; Marzieh Tavakol; et al. (BMC, 2017)
Abstract Background A number of scientific organisations have developed guidelines for the primary prevention of allergic disease through nutritional interventions. However, even if the best evidence-based guidelines are available, these guidelines do not necessarily lead to adherence and improved health outcomes. Method To determine how closely the practice of physicians in select Middle Eastern and North African countries compares with the current recommendations on the primary prevention of allergy a survey study was performed using a structured questionnaire and convenience sampling. Results A total of 1481 physicians responded, of which 66.1% were pediatricians. A total of 76.6% of responding physicians routinely identify infants who are at risk for developing allergy. In infants at risk for developing allergy, 89.1% recommend exclusive breastfeeding for at least 4 months. In contrast to current recommendations, 51.6% routinely recommend avoidance of any allergenic food in the lactating mother. In infants at risk of developing allergy who are completely formula fed, standard infant formula was recommended by 22.5% of responders. Of the responding physicians, 50.6% would recommend delaying the introduction of complementary food in infants at risk of allergy compared to those not at risk, whereas 62.5% would recommend postponing the introduction of potentially allergenic foods. Only 6.6% stated they follow all current recommendations on food allergy prevention. Conclusion The results of this survey suggest that a substantial part of responding physicians from select Middle Eastern and North African (MENA) countries do not follow current recommendations on primary prevention of allergic disease through nutritional interventions.